The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1029/2004jd004936
|View full text |Cite
|
Sign up to set email alerts
|

Flux and turbulence measurements at a densely built‐up site in Marseille: Heat, mass (water and carbon dioxide), and momentum

Abstract: [1] Eddy covariance (EC) observations above the densely built-up center of Marseille during the Expérience sur site pour contraindre les modèles de pollution atmosphérique et de transport d'émissions (ESCOMPTE) summertime measurement campaign extend current understanding of surface atmosphere exchanges in cities. The instrument array presented opportunities to address issues of the representativeness of local-scale fluxes in urban settings. Separate EC systems operated at two levels, and a telescoping tower al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
166
2
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 223 publications
(198 citation statements)
references
References 52 publications
(80 reference statements)
23
166
2
7
Order By: Relevance
“…Combining these previous steps results in an energy flux from traffic of 6.3 W m À2 per 10 mmol m À2 s À1 CO 2 . Following the CO 2 flux measurements of Grimmond et al [2004], the diurnal CO 2 flux values range from 10 mmol m À2 s À1 during the night to 30 mmol m À2 s À1 , which corresponds to a range of Q Fv between 6.3 (night) to 18.9 W m À2 (day). To determine hourly energy flux values from traffic it is then fitted (within its measurement errors) to the diurnal evolution of the measured CO 2 flux, resulting in a traffic induced anthropogenic heat of 5.3 W m À2 between 20 and 5 h GMT, a linear increase (decrease) between 5 and 8 h GMT (18 -20 h GMT) from 5.3 W m À2 to 18.9 W m À2 and a constant flux between 8 and 18 h GMT of 18.9 W m À2 , resulting in a daily mean of 12.3 W m À2 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Combining these previous steps results in an energy flux from traffic of 6.3 W m À2 per 10 mmol m À2 s À1 CO 2 . Following the CO 2 flux measurements of Grimmond et al [2004], the diurnal CO 2 flux values range from 10 mmol m À2 s À1 during the night to 30 mmol m À2 s À1 , which corresponds to a range of Q Fv between 6.3 (night) to 18.9 W m À2 (day). To determine hourly energy flux values from traffic it is then fitted (within its measurement errors) to the diurnal evolution of the measured CO 2 flux, resulting in a traffic induced anthropogenic heat of 5.3 W m À2 between 20 and 5 h GMT, a linear increase (decrease) between 5 and 8 h GMT (18 -20 h GMT) from 5.3 W m À2 to 18.9 W m À2 and a constant flux between 8 and 18 h GMT of 18.9 W m À2 , resulting in a daily mean of 12.3 W m À2 .…”
Section: Discussionmentioning
confidence: 99%
“…The absorption of CO 2 by vegetation during the day results in a negative (downward) CO 2 flux, which should be taken into account while interpreting the CO 2 measurements of Grimmond et al [2004] to obtain the ''pure'' traffic signal. Therefore we use the water use efficiency, which returns the amount of assimilated CO 2 per kg evaporated water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using measurements of CO 2 fluxes as an indication of human activity in the area, Grimmond et al (2004) Figure 7(b)). In a related study using data from the meso-NH mesoscale model and two intensive observation periods (21-23 and 24-26 June), Pigeon et al (2007) have shown that for a particular set of synoptic conditions (e.g.…”
Section: L: Obukhov Lengthmentioning
confidence: 99%